2021
DOI: 10.1175/jas-d-21-0040.1
|View full text |Cite
|
Sign up to set email alerts
|

Mean flow and turbulence characteristics of a nocturnal downburst recorded on a 213 m tall meteorological tower

Abstract: This study presents rare measurements and analysis of a nocturnal thunderstorm downburst on the 213 m tall Cabauw tower in The Netherlands. The event occurred on 12 March 2008 between 02:00 and 03:00 UTC and was measured using four ultrasonic 10-Hz anemometers positioned at 3, 60, 100, and 180 m above ground level. 1-second gusts in the outflow exceeded 30 m s−1 at 60 m and above. This wind event was accompanied by an abrupt change of wind direction from southwest to west. While the shift in wind direction cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…For example, in describing the morphology of downburst outflows, Hjelmfelt (1988) showed that the outflow velocity of laboratory jets measured by Poreh et al (1967) fall within the range of variations of outflow velocity of numerous downbursts measured during the Joint Airport Weather Studies (JAWS) field campaign. This kinematic similarity is also supported by Wood et al (2001), Romanic et al (2020), andRomanic andHangan (2020). Wood et al (2001) used the functional form of the outflow velocity proposed by Verhoff (1963) for a wall jet and provided a self-similar solution to the velocity field of a downburst.…”
Section: Introductionsupporting
confidence: 63%
“…For example, in describing the morphology of downburst outflows, Hjelmfelt (1988) showed that the outflow velocity of laboratory jets measured by Poreh et al (1967) fall within the range of variations of outflow velocity of numerous downbursts measured during the Joint Airport Weather Studies (JAWS) field campaign. This kinematic similarity is also supported by Wood et al (2001), Romanic et al (2020), andRomanic andHangan (2020). Wood et al (2001) used the functional form of the outflow velocity proposed by Verhoff (1963) for a wall jet and provided a self-similar solution to the velocity field of a downburst.…”
Section: Introductionsupporting
confidence: 63%
“…However, the presence of SV is not commonly observed in real downbursts. A weak SV is observed by Sherman [65] in his study of a weak downburst close to Brisbane, Australia, as well as by Romanic [66] in his study of severe microburst recorded on a 213-m tall tower in the Netherlands. The presence of the SV, preceding the passage of the PV, was also reported by Canepa et al [19] in the downburst event recorded in Genoa on May 13, 2018 by means of a LiDAR vertical profiler.…”
Section: Primary and Secondary Vorticesmentioning
confidence: 85%
“…However, these studies were based on data collected by anemometers located in coastal areas, and thus have similar roughness lengths with which it is difficult to detect a significant dependence on the roughness. Other studies carried out on different sites have shown increasing trends for the vertical profile of the turbulence intensity, as well as greater values comparable to those observed during synoptic events [45][46][47]. Moreover, it was shown that the vertical profile of the turbulence intensity on the height changes during the thunderstorm, showing a decreasing trend during the ramp-up phase of the wind speed [32].…”
Section: Thunderstorm Wind Velocity and Loading Modelingmentioning
confidence: 61%